Violence Prevention Programs Are Effective When Initiated During the Initial Workup of Patients in an Urban Level I Trauma Center. Issue 5 (September 2022) - Thomas, Yalaunda M.; Regan, Sheila C.; Quintana, Elena; Wisnieski, Elise; Salzman, Steven L.; Chow, Kevin L.; Mack, Charles F.; Stone, LeVon; Giloth, Barbara; Smith-Singares, Eduardo
This study represents the first attempt at evaluating the ability of the CureViolence Hospital-Response Intervention Program (previously CeaseFire) to disrupt the pattern of violent reinjury. The clinical data points of 300 African American men who presented to our trauma center with a gunshot wound and received intervention at the bedside between 2005 and 2007 (with a 48-month follow-up) were collected. This cohort was matched with a post hoc historical control group using hospital records from 2003 to 2005. The mean age for both groups was 23.9 years. Odds ratios and 95% confidence intervals were obtained. Using a binary logistical regression model, we assessed the performance of three variables of interest: age at the time of the initial injury, treatment group, and initial disposition group to predict recidivism. We utilized the Nagelkerke R square method, which described the proportion of the variance of the reinjury rate and validated our findings using the Hosmer–Lemeshow test (for goodness-of-fit). Six percent ( n = 18) of subjects in the treatment group and 11% ( n = 33) in the control group returned with a new injury, yielding a total reinjury rate of 8.5%. Most patients returned only once with another violent injury. Individuals who did not receive CureViolence services were nearly twice as likely (odds ratio = 1.94; 95% confidence interval = 1.065, 3.522) to return with a violent reinjury. This finding suggests that Hospital-Response Intervention Programs (HRIP) have a protective effect in violently injured patients. We therefore conclude our HRIP positively affected at-risk patients and prevented violent reinjury.